Comparison between Percutaneous Drainage vs Operative Intervention in Treatment of Appendicular Abscess: A Retrospective Study - Surrendar Dawani, Mansab Ali, Madiha Masood Khan, Salman Jafferi, Adeela Z Siddiqui, Rakesh Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the outcomes of percutaneous drainage and surgery in periappendiceal abscesses. Study design: A Retrospective study Place and Duration: This study was conducted at Jinnah Postgraduate Medical Centre Karachi Pakistan from January 2020 to December 2021. Methodology: For this study, we defined abscess as fluid collection adjacent to the appendix with 0-20 Hounsfield units (HU) attenuation on CT scan. Classification of Jeffrey, et al was used to grade abscesses. According to the classification patients with abscess or phlegmon, lesser than or equal to 3cm were represented in the grade 1 category. Grade 3 comprised those patients who had larger abscesses extending to the pelvic cavity. Patients of periappendiceal abscess aged above 16 years were enrolled for this study. The diagnosis was based on CT findings. The patient's discharge summary was used for confirmation. All the patients underwent two treatment options; Surgery or ultrasonography or CT-guided percutaneous drainage. Results: Out of 67 cases 44 (65.6%) cases underwent percutaneous drainage while 23 (34.3%) patients underwent surgery. Male participants were 37, 55.2% with a relative ratio of females (30, 44.7%). The mean symptoms onset was reported as 5 days ranging from 1-to 30 days. We observed that the percutaneous drainage group had 84.1% (37 cases) successful outcomes with a 15.9% (7 cases) failure ratio whereas only a single case of failure was observed by a surgery. Conclusion: Our results concluded that percutaneous drainage is effective for treating abscesses >6cm with a low risk of recurrence. However, this procedure lengthens the hospital stay until the complete resolution of the abscess.